When do we need to perform a diagnostic lumbar puncture for neurometabolic diseases? Positive yield and retrospective analysis from a tertiary center - Haliloğlu, Göknur; Vezir, Emine; Baydar, Leyla; Önol, Saniye; Sivri, Serap; Coşkun, Turgay; Topçu, Meral (The Turkish Journal of Pediatrics, 2012)
Neurometabolic diseases diagnosed by cerebrospinal fluid (CSF) examination are GLUT1 deficiency, serine-deficiency syndromes, glycine encephalopathy, cerebral folate deficiency, neonatal vitamin-responsive epileptic encephalopathies, disorders of monoamine metabolism, and y-amino butyric acid (GABA) metabolism. We retrospectively analyzed and compared the demographic, clinical, laboratory, and neuroimaging features of 62 patients in whom CSF examination was performed. Of the 62 patients, 16 (25.8%) had a final diagnosis, including succinic semialdehyde dehydrogenase (SSADH) deficiency (n=4), aromatic amino acid decarboxylase (AADC) deficiency (n=4), L-dopa-responsive dystonia (n=3), glycine encephalopathy (n=2), pyridoxal-phosphate-dependent seizures (n=l), cerebral folate deficiency (n=1), and serine biosynthesi defect (n=1). Parental consanguinity was present in all patients except one Positive yield of a diagnostic lumbar puncture (LP) for the diagnosis of inherited neurotransmitter metabolism disorder was 25.8% overall. Oculogyric crisis (50%), diurnal variation (81.8%) and consanguinity (93.8%) were the only statistically significant variables between patients with and without a specific diagnosis. It is challenging to diagnose neurotransmitter defects, since there is no ideal set of clinical symptoms. In our cohort, consanguinity, diurnal variation and abnormal ocular movements were the most significant findings associated with a diagnosis of a specific neurometabolic disorder based on CSF examination. Early diagnosis is of great importance not only for specific treatment, but also for genetic counseling and prenatal diagnosis.